Tournaments with Safeguards: A Blessing or a Curse for Women - Zhengyang Bao; Andreas Leibbrandt (Center for Economic Studies and ifo Institute (CESifo), 2020)
Workplace tournaments are one likely contributor to gender differences in labor market outcomes. Relative to men, women are often less eager to compete and thrive less under competitive pressure. We investigate a competitive workplace environment that may produce more gender-neutral outcomes: tournaments with safeguards. In our experiments, participants take part in a tournament with a real effort task and choose whether they want to have a complimentary safeguard that guarantees higher wages for the low-ranked. As expected, we find that women are more likely than men to obtain such a safeguard. However, obtaining a safeguard comes at a cost. On average, the safeguard causes lower performance, creates a gender wage gap, and over-proportionally disadvantages women. Thus, we provide novel evidence that easing women into tournaments can backfire.
Keywords: C92; J16; M52; 330; workplace tournaments; gender differences; safeguard; experiment